Internal Capabilities And External Sensitivity: A Strategic Formula For Digital Msme Growth In Central Java - Endang Sulistiyani; Talitha Dwi Wirastuti; Rustono Rustono; Taviyastuti; Linda Aprillianti (Citakonsultindo, 2025)
Knowledge sharing practices and readiness to change are crucial internal capabilities that contribute to successful innovation and organizational transformation. Market sensing, as a component of external sensitivity, is essential for responding to environmental changes. This research aims to determine the influence of knowledge sharing practices, readiness for change, and market sensing on the organizational performance of digital-based Micro, Small, and Medium Enterprises (MSMEs) in Central Java. The respondents included MSME entrepreneurs in the culinary, fashion, and craft sectors who utilize digital platforms. Data were collected through interviews, questionnaires, observation, and a literature review, and analyzed using Multiple Linear Regression. The results indicate that knowledge sharing practices, readiness to change, and market sensing each have a significant positive influence on organizational performance. Market sensing was found to be the most dominant factor. These findings suggest that integrating market sensing with a readiness for change, supported by internal knowledge sharing, fosters creative solutions and improves performance. This study empirically supports the Resource-Based View (RBV) theory by highlighting the strategic role of internal resources in achieving sustainable competitive advantage. The key implication is that for MSMEs to enhance adaptability, drive innovation, and respond effectively to market dynamics, they must develop internal capabilities that are deeply integrated with external sensitivity. These strategic efforts are essential for enhancing competitive advantage and ensuring sustained business growth amid the increasingly complex and rapidly evolving digital business environment.